Spontaneous head-to-tail cyclization of unprotected linear peptides with the KAHA ligation - Rohrbacher, Florian (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
The α-ketoacid–hydroxylamine (KAHA) ligation with 5-oxaproline enables the direct cyclization of peptides upon cleavage from a solid support, without coupling reagents, protecting groups, or purification of the linear precursors. This Fmoc SPPS-based method was applied to the synthesis of a library of 24 homoserine-containing cyclic peptides and was compared side-by-side with the synthesis of the same products using a standard method for cyclizing side-chain protected substrates. A detailed mechanistic study including (2)H and (18)O labeling experiments and the characterization of reaction intermediates by NMR and mass spectrometry is reported.